Self Compassion and Social Support Predict Body Dissatisfaction Among TikTok Emerging Adults: Rasa Belas Kasih Diri dan Dukungan Sosial Memprediksi Ketidakpuasan Terhadap Tubuh di Kalangan Remaja Pengguna TikTok - Alifia Davina Diwantari; Zaki Nur Fahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid digital development has increased social media usage, with TikTok becoming highly popular among individuals aged 18–29 years who are undergoing identity exploration and are vulnerable to appearance-related concerns. Specific Background: Exposure to idealized body-related content on TikTok is associated with body dissatisfaction, while internal and external psychological resources such as self compassion and social support are proposed as relevant factors. Knowledge Gap: Previous studies present contradictory findings regarding social support and rarely examine the simultaneous role of self compassion and social support among TikTok users in emerging adulthood. Aims: This study examined the relationship between self compassion and social support with body dissatisfaction among active TikTok users aged 18–29 years in East Java. Results: Using a quantitative approach with purposive sampling, data from 349 participants were analyzed through multiple linear regression. Findings revealed a significant simultaneous relationship between self compassion and social support with body dissatisfaction (p = 0.000 < 0.05), with a combined contribution of 75.2%. Self compassion demonstrated a larger partial contribution (53.4%) compared with social support (21.8%), and both variables showed negative regression coefficients, indicating that higher levels of these factors corresponded with lower body dissatisfaction. Novelty: This study provides empirical evidence demonstrating the simultaneous statistical contribution of internal and external psychological resources among TikTok users in emerging adulthood. Implications: The findings highlight the relevance of fostering self compassion and strengthening supportive interpersonal environments to address body dissatisfaction during identity development stages. Highlights: Internal Acceptance-Related Construct Contributed the Largest Statistical Proportion to Variance Explanation. Interpersonal Relational Resources Demonstrated Additional Measurable Contribution to Variance Explanation. Combined Statistical Model Explained More Than Three Quarters of Variance in Negative Body Perception. Keywords: Self Compassion, Social Support, Body Dissatisfaction, TikTok Users, Emerging Adulthood